The Effect of Public Speaking Program for Students at Nurussalam Islamic Modern Boarding School - Komarudin Komarudin; Zulaikah Zulaikah; Hastuti Retno Kuspiyah (Channing : Journal of English Language Education and Literature, 2019)
This research is a study of the public speaking program conducted at Nurussalam Islamic Boarding School. The purpose of this study is to know about how the Public Speaking program at Nurussalam Islamic Modern Boarding School and this research is qualitative research, in this research writer used the purposive sample, The writer only took the male students as the sample of research and with managers of the program that called as LAC and CLI, and the writer took the sample just for the students who are compulsory to speak English in public speaking, they are from class 3 until class 5, and The techniques of collecting the data used interview, observation, and documentation. The result of this study is an interest of the student in following that program, where public speaking programs are divided into 10 clubs and conducted only in two days it's Friday and Saturday with three languages are English, Arabic, Indonesian.